Maqāṣid Al-Sharī’ah And Sport: What It Means To The Practising Muslims - Abdul Sham Ahmad; Nurazzura Mohamad Diah; Wan Mohd Yusof Wan Chik; Baidruel Hairiel Abd Rahim (USIM Press, 2024)
VOL. 28 NO. 1 Page (16-31)